PROTOTYPE OF HOSPITAL WASTE MEASUREMENTS INTEGRATED BASED ON ISO 14001 - Muhammad Rifai Rifai; Muhammad Qomaruddin Qomaruddin; Arief Marwanto Marwanto; Barry Nur Setyanto Nur Setyanto (Journal of Telematics and Informatics, 2022)
One of the water pollution is wastewater that comes from hospitals. The surrounding community can suffer from this disease because hospital wastewater contains quite high organic compounds also contains other chemical compounds as well as pathogenic microorganisms. stabilize the pH. The levels of pH, TDS, and TSS can also be affected by the concentration of wastewater. The higher the dilution rate of the wastewater, the lower the pH, TDS, and TSS levels will also be higher. The results of the test with 4 different water media showed that the pH, TDS and TSS sensors were able to work well where in tap water and coffee showed normal results and stale tea water and betadine water is not normal. The pH, TDS, TSS sensors are able to detect normal water conditions in tap water and coffee with a pH value of 6.89 to 5.41 TDS 179.71 to 279.41 ppm and TSS 1.00 ntu to 16.00 ntu. pH, TDS, and TSS sensors are also able to detect abnormal water conditions in stale tea water and betadine water with a pH ranging from 4.24 – 4.56 TDS 246.11 ppm – 1129 ,54 ppm and TSS 7 ntu – 13 ntu. These values ​​are in accordance with the liquid waste quality standards that have been set in the regulation of the Minister of Health of the Republic of Indonesia number 7 of 2019 concerning hospital environmental health